Social Media Sentiments of Real Estate Investment on Blockchain Technology in Post-COVID-19 - Siriphen, Supharoek; Chandarasupsang, Tirapot; Tananchana, Annop; Ramasamy, Siva Shankar; Dawod, Ahmad Yahya (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The real estate sector is experiencing significant transformation in response to the impact of COVID-19, emphasizing the need for innovative approaches. This study examines the public’s sentiment towards the adoption of blockchain technology, particularly digital tokens, for real estate investment in the post-pandemic era. Digital tokens offer numerous advantages, including fractional ownership, asset tokenization, real estate crowdfunding, streamlined property transactions, efficient rental management, enhanced property title records, and the creation of Real Estate Investment Trusts (REITs). These advantages could be realized by leveraging blockchain technology, resulting in enhanced liquidity, accessibility, transparency, and efficiency in the real estate sector. This article analyzed the sentiments expressed on social network platforms to understand the perceived benefits of utilizing blockchain-based digital tokens in real estate. Additionally, practical considerations related to the implementation of blockchain technology in the real estate sector were discussed, shedding light on the potentially transformative impact of this technology on the industry.